BUGINESE ETHNOMATHEMATICS: BARONGKO CAKE EXPLORATIONS AS MATHEMATICS LEARNING RESOURCES - Pathuddin, Hikmawati; Kamariah, Kamariah; Nawawi, M. Ichsan (Journal on Mathematics Education, 2021)
Mathematics is still viewed as a culture-free subject. This forms a negative perception for students on mathematics. Most students assume that mathematics and culture are not related. This may occur because mathematics taught in school is not contextual and far from the reality of everyday life. Historically, mathematics has become a part of everyday life. As a maritime nation, Indonesia has a diverse culture. But many teachers are not yet aware of the integration of the culture into mathematics learning. Barongko cake is one of the Buginese cultural heritages. Buginese people have unconsciously been practicing mathematics in making these cakes. Therefore, this research aims to explore activities in making Barongko cakes in the Buginese community that involves mathematical concepts. This research is a qualitative descriptive with an ethnographic approach. The data collection methods are carried out through observation, documentation, interview with an expert in making Barongko cake. This research found that Barongko making process involves mathematics in the concept of division, congruence, and similarity, as well as a triangular prism, and half sphere. This cake has the potential to be used as a source of contextual mathematics learning in schools.